Wnt/β-Catenin Signaling as a Molecular Target by Pathogenic Bacteria - Silva-García, Octavio; Valdez-Alarcón, Juan J.; Baizabal-Aguirre, Víctor M. (Frontiers in Immunology, 2019)
The Wnt/b-catenin signaling pathway is crucial to regulate cell proliferation and polarity, cell determination, and tissue homeostasis. The activation of Wnt/b-catenin signaling is based on the interaction between Wnt glycoproteins and seven transmembrane receptors—Frizzled (Fzd). This binding promotes recruitment of the scaffolding protein Disheveled (Dvl), which results in the phosphorylation of the co-receptor LRP5/6. The resultant molecular complex Wnt-Fzd-LRP5/6-Dvl forms a structural region for Axin interaction that disrupts Axin-mediated phosphorylation/degradation of the transcriptional co-activator -catenin, thereby allowing it to stabilize and accumulate in the nucleus where it activates the expression of Wnt-dependent genes. Due to the prominent physiological function, the Wnt/β-catenin signaling must be strictly controlled because its dysregulation, which is caused by different stimuli, may lead to alterations in cell proliferation, apoptosis, and inflammation-associated cancer. Pathogenic bacteria employ a variety of molecular strategies to alter the appropriate functioning of diverse signaling pathways. Among these, Wnt/β-catenin has recently emerged as an important target of several virulence factors produced by bacteria. The mechanisms used by these factors to interfere with the activity of Wnt/β-catenin is diverse and include the repression of Wnt inhibitors’ expression by the epigenetic modification of histones, blocking Wnt-Fzd ligand binding, activation or inhibition of β-catenin nuclear translocation, down- or up-regulation of Wnt family members, and inhibition of Axin-1 expression that promotes β-catenin activity. Such a variety of mechanisms illustrate an evolutionary co-adaptation of eukaryotic molecular, signaling to a battery of soluble or structural components synthesized by pathogenic bacteria. This review gathers the recent efforts to elucidate the mechanistic details through which bacterial virulence factors modulate Wnt/β-catenin signaling and its physiological consequences concerning the inflammatory response and cancer.